RESILIENSI ATLET PARAGAME YANG BERPRESTASI DI TINGKAT NASIONAL DAN INTERNASIONAL - Hendrizal Aganta; Untung Subroto (STKIP Subang, 2024)
This study aims to look at the description of resilience in Paragame athletes who have achieved national and international achievements. Resilience is defined as an individual's ability to bounce back, survive, and thrive when facing challenges and pressures. This research was conducted using a qualitative approach with phenomenological methods to explore the in-depth experiences of five Paragame athletes who have different disability backgrounds. Data were obtained through interviews and observations and analyzed based on seven dimensions of resilience, including emotional control, impulse control, optimism, causal analysis, empathy, self-efficacy, and the ability to bounce back. The results showed that of all the five research subjects, namely, R, I, A, S, AH fulfilled the seven dimensions of resilience, namely Emotional regulation, Impulse Control, Optimism, Casual Analysis, Self Efficacy, Reaching Out. The results of this study also show that all of the research subjects above fulfill the three components of resilience, namely I have, I am, I can.